A genetic algorithm approach for timetabling problem: the time group strategy - Md Sultan, Abu Bakar; Mahmod, Ramlan; Sulaiman, Md. Nasir; Abu Bakar, Mohd Rizam (Universiti Utara Malaysia Press, 2004)
The university timetabling problems (TTP) deal with the scheduling of the teaching program. Over the last decade variant of Genetic Algorithm (GA) approaches have been used to solve various types of TTP with great success. Most of the approaches are problem dependent, applied only to the institutions where they were designed. In this paper we proposed time group strategy and Simple GA (TGGA) to solve highly constrained TTP. The proposed model promises to solve highly constrained timetabling with less effort. The model is tested and results are discussed.